Stock assessment of the penaeid prawn Metapenaeus monoceros Fabricius along the Indian coast - Sukumaran, K K; Deshmukh, V D; Rao, G Sudhakara; Alagaraja, K; Sathianandan, T V (Indian Journal of Fisheries, 2011)
The annual average production oi Metapenaeus monoceros during 1985-89 was 10 286 tonnes,nearly 7.2% of the penaeid prawn landings in the country. Tlie west coast accounted for 71.2% and theeast coast for the rest. Among the maritime states, Maharashtra ranked first in production (27.2%)followed by Kamataka (22.3%) and Andhra Pradesh (21.3 %). The estimates of von Benalanffy growthparameters, L" and K (annual) were 180 mm and 1.8 for males, and 210 mm and 1.8 for females. Thisprawn attained a size of 149 mm and 173 mm in males and females, respectively, at the end of 1 year.The instantaneous total mortality coefficient (Z) ranged between 4.28 and 8.05 in males, and between4.17 and 6.33 in females. Natural mortality coefficient (M) was 1.8 in both the sexes. Yield per recruitstudies indicated that for an age of 0.59 year at first capture the fishery generated a steadily increasingyield up to 10 000 tonnes for an annual effort of 1 578 000 boat trips (16 670 000 fishing hours) atwhich the annual fishing mortality (F) is 3.76 and the exploitation ratio (E) is 0.67. Beyond this levelof exploitation the increase in yield was only marginal. Even though the average aimual yield during1985-89 was marginally lower than the maximum sustainable yield (MSY) of 10 993 t, the catchduring 1987 and 1988 exceeded MSY level. Hence the desirability of maintaining the effort at thepresent level to obtain sustainable yields is mentioned.